Validation and comparison of reference genes for qPCR normalization of celery (Apium graveolens) at different development stages - Meng-Yao eLi; Feng eWang; Qian eJiang; Guang-Long eWang; Chang eTian; Ai-Sheng eXiong (Frontiers in Plant Science, 2016)
A suitable reference gene is an important prerequisite for guarantying accurate and reliable results in qPCR analysis. Celery is one of the representative vegetable in Apiaceae and is widely cultivated and consumed in the world. However, no reports have been previously published concerning reference genes in celery. In this study, the expression stabilities of nine candidate reference genes in leaf blade and petiole at different development stages were evaluated using three statistics algorithms geNorm, NormFinder, and BestKeeper. Our results showed that TUB-B, TUB-A, and UBC were the most reference genes among all tested samples. GAPDH represented the maximum stability for most individual sample, while the UBQ displayed the minimum stability. To further validate the stability of reference genes, the expression pattern of AgAP2-2 was calculated by using the selected genes for normalization. In addition, the expression patterns of several development-related genes were studied using the selected reference gene. Our results will be beneficial for further studies on gene transcription in celery.